The Effect of Academic Supervision to School Supervisors and Teacher Motivation on Teacher Performance - Nadrah, Nadrah (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study is to describe the influence of school supervisors' academic supervision and motivation teacher achievement on teacher performance at SMA Negeri Mamajang District, Makassar City. This type of research is research ex post facto using a quantitative approach. Sampling technique was carried out by using proportional random sampling . The total population in this study was 247 teachers, where exogenous variable in this study is supervision academic supervisor of the school, while the intervening variable is teacher achievement motivation and the endogenous variable is teacher performance. The research instrument used is a questionnaire, the data were analyzed using descriptive and inferential statistics, which are in the analysis the inferential use analysis track.. Study This aim (1) For get description about academic supervision of school supervisors, teacher achievement motivation and teacher performance at the District Public High School Mamajang Makassar City (2) to find out that empirically supervision academic supervisor school effect on teacher achievement motivation at SMA Negeri Mamajang District, Makassar City (3) for obtain information empirical that supervision academic supervisor school influential to performance Teacher on senior high school Country Subdistrict Mamajang City Macassar (4) For ensure that in a manner empirical motivation achievement Teacher influential to performance Teacher on senior high school country subdistrict mamajang city macassar (5) for confirms that empirically the academic supervision of school supervisors influences teacher performance through motivation achievement teacher on senior high school Country Mamajang District City Macassar. Results study show that (1) supervision academic supervisor school with mark average as big 104.49 and generally in the good category, teacher achievement motivation with an average value of 111.20 And in general are in the very good category, while teacher performance with an average score of 129.23 and in general are in the very good category. (2) there is a direct influence from the supervisor's academic supervision school on teacher achievement motivation of 75.3% with a path coefficient of 0.868; (3) there is influence direct supervision academic supervisor school to performance Teacher as big 2,3 % with coefficient track 0.153; (4) there is a direct effect of teacher achievement motivation on teacher performance of 87.4% with a path coefficient 0.838; (5) there is an indirect effect of the school supervisor's academic supervision on teacher performance through motivation teacher achievement of 3,4 % with coefficients track 0, 111.